Phosphorylation at threonine-235 by a ras-dependent mitogen-activated protein kinase cascade is essential for transcription factor NF-IL6. - Nakajima, T (1993)
NF-IL6, a member of the basic leucine zipper (bZIP) family transcription factors, is involved in expression of inducible genes involved in immune and inflammatory responses. We observed that coexpression of oncogenic p21ras stimulated the transactivating activity of NF-IL6 and induced phosphorylation of Thr-235 located just N-terminal to the DNA binding domain of NF-IL6. Recently, mitogen-activated protein (MAP) kinases have been shown to be implicated in the cellular response to activated ras. Purified MAP kinases specifically phosphorylated Thr-235 of NF-IL6 in vitro. Mutation of Thr-235 abolished the ras-dependent activation of NF-IL6. From these results, we conclude that NF-IL6 is regulated through phosphorylation by MAP kinases in response to activated ras.